Cryptogamic stem covers may contribute to nitrous oxide consumption by mature beech trees - Machacova, Katerina; Maier, Martin; Svobodova, Katerina; Lang, Friederike; Urban, Otmar (Scientific reports, 2017)
Naturally produced by microbial processes in soil, nitrous oxide (N2O) is an important greenhouse gas contributing to climate change. Accordingly, there is a need to accurately quantify the capability of forest ecosystems to exchange N2O with the atmosphere. While N2O emissions from soils have been well studied, trees have so far been overlooked in N2O inventories. Here, we show that stems of mature beech trees (Fagus sylvatica) may act as a substantial sink of N2O from the atmosphere under conditions of soils consuming N2O. Consistent consumption of N2O by all stems investigated (ranging between -2.4 and -3.8 µg m-2 h-1) is a novel finding in contrast to current studies presenting trees as N2O emitters. To understand these fluxes, N2O exchange of photoautotrophic organisms associated with beech bark (lichens, mosses and algae) was quantified under laboratory conditions. All these organisms were net N2O sinks at full rehydration and temperature of 25 °C. The consumption rates were comparable to stem consumption rates measured under field conditions. Cryptogamic stem covers could be a relevant sink of N2O in European beech forests.
Keywords: oxid dusný; oxid uhličitý; stromy; Evropa; půdní mikrobiologie; Europe; Fagus; Greenhouse Gases; skleníkové plyny; Trees; autotrofní procesy; Nitrous Oxide; Carbon Dioxide; půda; Soil Microbiology; buk (rod); Autotrophic Processes; Soil